PENERAPAN TEORI KENDALI PADA MASALAH PROGRAM DINAMIK - Pardi Affandi; Dewi Anggraini; Nur Salam (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2012)
This study examines the application of Control Theory to the problem of Dynamic Program. Dynamic program is a design analysis in math to determine a series decisions relating to the decision-making process are gradually double to optimize problem solving effectively. Classic problems in dynamic programming is the concept of phase, state and acquisition. Problem solving will use Control Theory.